2019
DOI: 10.1002/lary.27873
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of carotid‐sparing IMRT for T1 glottic cancer: Comparison with conventional radiation

Abstract: Objectives: We aim to report oncologic outcomes after conventional radiotherapy (ConRT) using opposed lateral beams and intensity-modulated radiation therapy (IMRT) for tumor (T)1 nodal (N)0 T1 N0 glottic squamous cell carcinoma.Study Design: Retrospective case-control study. Methods: We retrospectively reviewed demographic, disease, and treatment characteristics for patients treated at our institution during 2000 to 2013.Results: One hundred fifty-three patients (71%) were treated using ConRT and 62 (29%) usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 40 publications
1
28
0
1
Order By: Relevance
“…For example, a Surveillance, Epidemiology, and End Results (SEER)‐Medicare study showed that the 10‐year risk of cerebrovascular events for patients with head and neck cancer was 34% after conventionally delivered definitive RT vs 26% after surgery alone ( P < .01) 39 . A recent series from our group on T1 glottic cancer showed no cerebrovascular events among patients treated with carotid‐sparing IMRT vs 3% among patients treated with conventional RT 17 . In the current T2 series, only two patients developed a carotid event several years after RT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a Surveillance, Epidemiology, and End Results (SEER)‐Medicare study showed that the 10‐year risk of cerebrovascular events for patients with head and neck cancer was 34% after conventionally delivered definitive RT vs 26% after surgery alone ( P < .01) 39 . A recent series from our group on T1 glottic cancer showed no cerebrovascular events among patients treated with carotid‐sparing IMRT vs 3% among patients treated with conventional RT 17 . In the current T2 series, only two patients developed a carotid event several years after RT.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, for glottic cancer, the use of IMRT has been driven mainly by a desire to reduce the dose to the carotid arteries, which is hoped to reduce the risk of subsequent stroke 13‐16 . At our institution, IMRT is used to treat T1 glottic cancer for carotid artery dose sparing and has led to excellent oncologic outcomes 17 . Although IMRT may be beneficial for T1 disease, it may not be ideal for all patients with T2 disease, especially those with bulky disease, with the corresponding increases in uncertainties in target delineation and risk of missing subclinical disease at the primary site or adjacent lymph nodes 18 …”
Section: Introductionmentioning
confidence: 99%
“…In the setting of early stage glottic SCC, IMRT has the potential to reduce dose to the carotid arteries, which would potentially decrease the risk of stroke and more easily allow for future RT in the event of a second head and neck cancer diagnosis [4,[6][7][8][9][10][11]. Others have shown that clinical outcomes are not compromised with IMRT, and dosimetric analyses demonstrate significant dose reduction to the carotid arteries by up to 75% [4,13,19,20]. Mohamed et al performed a retrospective case-control study comparing 3DCRT and IMRT, showing no statistically significant difference in oncologic outcomes (e.g., 3-year locoregional control and OS); however, there was also no statistically significant difference in the rate of cerebrovascular events (p = 0.7), feeding tube dependence (p = 0.5) or aspiration events (p = 0.4) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that clinical outcomes are not compromised with IMRT, and dosimetric analyses demonstrate significant dose reduction to the carotid arteries by up to 75% [4,13,19,20]. Mohamed et al performed a retrospective case-control study comparing 3DCRT and IMRT, showing no statistically significant difference in oncologic outcomes (e.g., 3-year locoregional control and OS); however, there was also no statistically significant difference in the rate of cerebrovascular events (p = 0.7), feeding tube dependence (p = 0.5) or aspiration events (p = 0.4) [19]. Zumsteg et al also performed a clinical comparison of IMRT and 3DCRT and found no difference in oncologic outcomes, with 3-year local control rates of 88% and 89%, respectively (p = 0.938), while maintaining low doses to the carotid arteries [13].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with EGSCC have shown excellent local control (LC) and survival rates, with voice quality preservation and low toxicity levels after undergoing RT (2); thus, RT is the preferred treatment option among these patients (3,4). Although RT is widely accepted as the treatment of choice for early glottic cancer, it varies greatly with respect to dose, dose per fraction, and treatment techniques (5)(6)(7)(8)(9). The accelerated repopulation of surviving clonogenic tumor cells during the RT period, known to be a key factor determining the LC rate in head and neck cancer, has also been observed in patients with early glottic carcinomas.…”
mentioning
confidence: 99%